The Level of Practicing Transformational Decision Making Process by Secondary School Principals in Amman Governorate and its Relation to the Level of their Motivation Towards Work - Dawani, Kamaljo; Al-Sharefy, Abbas (Jordan Journal of Educational Sciences, 2012)
This study aimed at finding out the level of practicing transformational decision-making process by secondary school principals in Amman governorate and its relation to the level of their motivation towards work. The sample consisted of (100) male and female secondary school principals. They were randomly drawn by using proportional stratified random sample from the population of the study. Two instruments were used: the first was “Decision-making Self-Assessment Questionnaire”, and the second was “Principals’ Motivation towards work Questionnaire”. The findings of the study showed that the level of practicing transformational decision-making process by secondary school principals was medium (Mean: 2.97, Sd.: 1.07). the level of principals’ motivation towards work was high, (Mean: 4.01, sd: 0.67). Finally, there was a significant positive relationship at (  0.001) between the level of practicing transformational decision making process by the principals and their level of motivation towards work. The value of the correlation coefficient was (0.98). Recommendations of the study : Organizing seminars for secondary school principals, pertaining to transformational decision-making in particular and to the theory of transformational leadership in general, conducting similar studies in Jordanian public and private universities, in light of age, gender, experience, and academic qualifications variables should be exposed to the concept of motivation and its relation to work quality and to their morale.